Loss of the ‘Self’ as a Social and Ethical Challenge. Findings from the London ‘Music for Life’ Project (Global Journal of Human-Social Science, 2023)
The following considerations describe the findings of a qualitative research project that accompanied a course of the Wigmore Hall Initiative Music for Life in a long-term study on music and dementia The project succeeds in reconstructing a learning process that affects both musicians and caregivers and is able at least selectively to integrate people living with dementia A learning process which captures the inter-professional team creating moments that people with dementia also experience as highlights could be observed in the successive experience levels ofestablishing identity deepening communication doing participation and opening the chance for development within an astonishing Community of Practice
Keywords: music– people living with dementia – identity –communication–participation–development–community of practice